Crack resistance curve in glass matrix composite reinforced by long Nicalon (R) fibres - Dlouhy, Ivo; Kotoul, Michal; Vyslouzil, Tomas; Chlup, Zdenek; Boccaccini, Aldo R. (Journal of Materials Science, 2008)
Theoretical micromechanical analysis of bridged crack development at chevron-notch tip of three-point bend specimens has been applied to determine the crack resistance curve for a composite made of a glass matrix reinforced by continuous Nicalon® fibres. Fracture toughness (K IC) values were determined using the chevron-notch technique at room temperature. The theoretical predictions were based on micromechanical analysis exploiting weight functions. Detailed FEM analysis using the ANSYS package was applied to determine numerically the weight functions for orthotropic materials. Appropriate bridging models for the theoretical prediction of the R-curve behaviour typical of the investigated composite were applied together with the weight functions. Experimental observations confirmed the theoretical calculations. © 2008 Springer Science+Business Media, LLC.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.crackr